Dentine collagen cross-linking using tiopronin-protected Au/EDC nanoparticles formulations. Issue 7 (July 2019) - Daood, U.; Akram, Z.; Matinlinna, J.P.; Fawzy, A.S.
Highlights: Crosslinking with TPAu/EDC significantly improved the biodegradation resistance and proteases inhibition of demineralized dentine. Crosslinking with TPAu/EDC enhances the mechanical and structural stability of demineralized dentine. Dentine collagen crosslinking effect is dependent on TPAu/EDC ratio. Abstract: Objective: The aim of this study was to investigate EDC-assisted collagen crosslinking effect with different concentrations of tiopronin-protected gold (TPAu) nanoparticles on demineralized dentine. Methods: TPAu nanoparticles were fabricated from 0.31-g tetrachloroauric acid and 0.38-g of N -(2-mercaptopropionyl) glycine (2.4-mmol). Then co-dissolved using 35-mL of 6:1 methanol/acetic acid and mixed using NaBH4 . EDC (0.3-M) was conjugated to TPAu nanoparticles at TPAU/EDC-0.25:1, and TPAU/EDC-0.5:1 treatment formulations ratios. Dentin specimens treated with 0.3-M EDC solution alone or left untreated were used as control. Nanoparticles formulations were characterized in term of particles morphology and size, Zeta potential, thermogravimetric analysis and small-angle X-ray scattering. Dentin substrates were characterized in term of TEM investigation, dentin proteases characterization, hydroxyproline liberation, elastic modulus measurement, Raman analysis and confocal microscopy viewing. Results: TEM evaluation of tiopronin protected gold nanoparticles dispersion revealed nano-clusters formations in both groups. However, based on our TEM measurements, the particle-size was ranging from ˜20 to 50 nm with spherical core-shape which were almost similar for both TPAu/EDC ratios (0.5:1 and 0.25:1). Zeta potential measurements indicate negative nanoparticles surface charge. SAXS profiles for both formulations, suggest a typical profile for uni-lamellar nanoparticles. Superior dentin collagen cross-linking effect was found with the TPAu/EDC nanoparticles formulations compared to the control and EDC treated groups. Significance: Cross-linking of dentin collagen using TPAu coupled with EDC through TPAu/EDC nanoparticles formulations is of potential significance in improving the biodegradation resistance, proteases inhibition, mechanical and structural stability of demineralized dentin substrates. In addition, the cross-linking effect is dependent on TPAu/EDC ratio, whereas higher cross-linking effect was found at TPAu/EDC ratio of 0.5:1.